Classification and Rating of Inclusions in a High Carbon Steel - M. Faraji (The Minerals, Metals and Materials Society, 2010)
Inclusions formed in a high-carbon, manganese-silicon killed plain steel (Fe-0.77C wt%) were studied. Various techniques were used to characterise the inclusions, and the latter were classified according to their chemical composition, size and morphology. The main constituent elements entering the inclusions were Mn, S, Al, and oxygen. Alongside MnS and some Al2O3 inclusions many non-metallic inclusions appeared in complex forms, consisting of silicates, sulphides and oxides. Duplex oxy-sulphides, mainly MnS combined with Al2O3, or SiO2 were the most common complex multiphase inclusions in this steel. The nanoindentation technique was used to assess and rate different types of inclusions and data of the hardness and elastic modulus of individual inclusions at room temperature are presented.